Redesigning the Business Model for the Distribution of Non-Subsidized Fertilizer Based on the Business Model Canvas in the Riau Province - Oktiviani Oktiviani; Arman Hakim Nasution (Journal of Social Research, 2026)
The non-subsidized fertilizer distribution sector in Riau Province faces increasing market demand along with significant challenges related to supply fulfillment, service quality, and business process efficiency. CV Bangun Dinata, as one of the official distributors of non-subsidized fertilizers, experiences limitations within its existing business model, including manual operational processes, unintegrated distribution channels, limited information transparency, and high order cancellation rates. This study aims to redesign the non-subsidized fertilizer distribution business model using the Business Model Canvas (BMC) framework to develop a more adaptive, competitive, and customer-oriented business strategy. This research employed a qualitative case study approach involving interviews, observations, questionnaires, and document analysis. Data were collected from company stakeholders and 30 fertilizer agents using purposive sampling techniques. The analysis process consisted of existing Business Model Canvas mapping, SWOT analysis, gap analysis, identification of Critical Success Factors (CSFs), and development of a proposed To-Be business model validated through service blueprint analysis and operational impact simulation. The results indicate that the existing business model requires improvement, particularly in value propositions, digital channel integration, customer relationship management, and operational activities. The proposed redesign transforms the company from a product-oriented model into a service-oriented business model by implementing digital ordering systems, real-time inventory information, delivery tracking, flexible payment mechanisms, and responsive customer service. The implementation simulation demonstrates potential improvements in fulfillment rates, operational efficiency, and customer satisfaction. In conclusion, the redesigned Business Model Canvas provides a strategic framework for improving distribution performance, strengthening competitiveness, and supporting sustainable business growth for CV Bangun Dinata.